THE ANGRY YOUNG MEN MOVEMENT: POST-WAR LITERARY REBELLION AND ITS CULTURAL IMPACT - Chinakov Abdulahad Mo‘minjon ugli (TADQIQOTLAR, 2025)
The "Angry Young Men" movement emerged in post-World War II Britain as a cultural and literary phenomenon, capturing the frustrations and aspirations of a generation disillusioned by traditional values and societal constraints. This study examines the historical context, defining characteristics, and enduring legacy of the movement, emphasizing its impact on literature and broader cultural discourse.